Biological monitoring of foundry workers exposed to polycyclic aromatic hydrocarbons. Issue 7 (July 1990) - Sherson, D; Sabro, P; Sigsgaard, T; Johansen, F; Autrup, H
Abstract : This investigation describes benzo(a)pyrene (BP) serum protein adduct concentrations in 45 foundry workers and 45 matched non-occupationally exposed controls. High and low BP exposure groups were defined using breathing zone hygienic samples for both quartz and BP exposures. A newly developed enzyme linked immunosorbent assay detected benzo(a)pyrenediolepoxide-I binding to serum protein. Mean BP protein adduct concentrations (SD) for non-smoking (24.0 BP equivalents/100 micrograms protein (21.0] and smoking (28.0 (18.2] foundry workers were significantly higher than mean values for non-smoking (7.23 (8.72] and smoking (14.2 (24.4] controls. Foundry workers with high exposures to either quartz (28.4 (15.5] or BP (30.7 (19.3] had slightly raised mean adduct concentrations compared with foundry workers with low exposure for quartz (23.9 (23.1] or BP (24.5 (19.4). Highest mean adduct concentrations were found among a small group of workers with simultaneous high exposures to both quartz and BP (39.2 (6.5] suggesting an additive effect. These data support the ideas of a possible aetiological connection between an increased risk of lung cancer and BP exposure among foundry workers, and an additive effect between BP and quartz. Measurement of BP serum protein adduct concentrations appears to be a useful method by which groups exposed to BP may be biologically monitored.